Vital signal sensing and manipulation of a microscale organ with a multifunctional soft gripper - Roh, Yeonwook; Kim, Minho; Won, Sang Min; Lim, Daseul; Hong, Insic; Lee, Seunggon; Kim, Taewi; Kim, Changhwan; Lee, Doohoe; Im, Sunghoon; Lee, Gunhee; Kim, Dongjin; et al. (Science Robotics, 2021)
Soft grippers that incorporate functional materials are important in the development of mechanically compliant and multifunctional interfaces for both sensing and stimulating soft objects and organisms. In particular, the capability for firm and delicate grasping of soft cells and organs without mechanical damage is essential to identify the condition of and monitor meaningful biosignals from objects. Here, we report a millimeter-scale soft gripper based on a shape memory polymer that enables manipulating a heavy object (payload-to-weight ratio up to 6400) and grasping organisms at the micro/milliscale. The silver nanowires and crack-based strain sensor embedded in this soft gripper enable simultaneous measurement of the temperature and pressure on grasped objects and offer temperature and mechanical stimuli for the grasped object. We validate our miniaturized soft gripper by demonstrating that it can grasp a snail egg while simultaneously applying a moderate temperature stimulation to induce hatching process and monitor the heart rate of a newborn snail. The results present the potential for widespread utility of soft grippers in the area of biomedical engineering, especially in the development of conditional or closed-loop interfacing with microscale biotissues and organisms.
Keywords: Biosignals; Compliant interfaces; Condition; Grasped object; Mechanical damages; Millimeter-scale; Multi-functional interfaces; Shape memory polymers; Soft objects; Vital signals; Animals; Bioengineering; Biomedical Engineering; Biomimetics; Biotechnology; Calibration; Elastic Modulus; Equipment Design; Hand Strength; Humans; Man-Machine Systems; Materials Testing; Nanowires; Pressure; Robotics; Smart Materials; Snails; Stress, Mechanical; Temperature